2005
DOI: 10.1016/j.cell.2004.12.025
|View full text |Cite
|
Sign up to set email alerts
|

The F Box Protein Dsg1/Mdm30 Is a Transcriptional Coactivator that Stimulates Gal4 Turnover and Cotranscriptional mRNA Processing

Abstract: We report here that the prototypical yeast transcription factor Gal4 undergoes two distinct modes of ubiquitin-mediated proteolysis: one that occurs independent of transcription and restricts Gal4 function, and another that is transcription coupled and essential for productive activation of Gal4 target genes. Destruction of transcriptionally active Gal4 depends on an F box protein called Dsg1/Mdm30. In the absence of Dsg1, Gal4 is stable, nonubiquitylated, and unable to productively stimulate transcription. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
172
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 155 publications
(183 citation statements)
references
References 45 publications
10
172
1
Order By: Relevance
“…In this view, polyubiquitinated forms might be targeted for degradation, whereas a transient state of mono-ubiquitination might regulate protein activity before its targeting for degradation. Ubiquitination has been linked to the regulation of the activity of some transcription factors (Bres et al, 2003;Greer et al, 2003;Peloponese et al, 2004;Muratani et al, 2005). Furthermore, ubiquitination is reported to be essential to the activity of the TADs of the VP16 and Tat proteins (Salghetti et al, 2001;Bres et al, 2003), and ubiquitination of these TADs has been shown to increase their interaction with the positive transcription elongation factor b (P-TEFb), thus augmenting the rate of transcription elongation (Kurosu and Peterlin, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In this view, polyubiquitinated forms might be targeted for degradation, whereas a transient state of mono-ubiquitination might regulate protein activity before its targeting for degradation. Ubiquitination has been linked to the regulation of the activity of some transcription factors (Bres et al, 2003;Greer et al, 2003;Peloponese et al, 2004;Muratani et al, 2005). Furthermore, ubiquitination is reported to be essential to the activity of the TADs of the VP16 and Tat proteins (Salghetti et al, 2001;Bres et al, 2003), and ubiquitination of these TADs has been shown to increase their interaction with the positive transcription elongation factor b (P-TEFb), thus augmenting the rate of transcription elongation (Kurosu and Peterlin, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, SCF Cdc4 -mediated degradation of Gcn4 illustrates the "OR" mode of control because it requires CPD phosphorylation by either Srb10 or Pho85 (Meimoun et al, 2000;Chi et al, 2001). Recently, another OR mode, involving a protein having two or more degrons that are regulated by different SCF complexes, has been described for Gal4p (Muratani et al, 2005). In this case, SCF Grr1 facilitates turnover of Gal4p at a relatively slow rate during yeast cell growth in the presence of a noninducing carbon source, whereas SCF Dsg1/Mdm30 mediates rapid degradation of a differentially phosphorylated form of Gal4p during growth in the presence of galactose (Muratani et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of wild-type Hac1p and the various mutant Hac1p proteins was performed using a polyclonal anti-Hac1p antibody (Kawahara et al, 1997) or an anti-Hac1p i tail antibody . Analysis of Ura3/HA and Hac1/HA fusion proteins used anti-hemagglutinin (HA) tag antibodies, (Muratani et al, 2005), whereas detection of green fluorescent protein (GFP) fusion proteins used polyclonal anti GFP antibodies (a gift from Pamela Silver, Dana-Farber Institute, Boston, MA). Subsequently, the membranes were probed with monoclonal anti-glyceraldehyde-3-phosphate dehydrogenase (GAPDH) (a gift from Trevor Lithgow, University of Melbourne, Melbourne, Australia) as a control for protein loading.…”
Section: Cell Extracts and Immunoblottingmentioning
confidence: 99%
See 2 more Smart Citations